Use of Temporal Codes Computed from a Cochlear Model for Speech Recognition - Deng, Li; Sheikhzadeh, H. (Listening to Speech: An Auditory Perspective, 2006)
The human species is largely defined by its use of spoken language, so integral is speech communication to behavior and social interaction. Despite its importance in everyday life, comparatively little is known about the auditory mechanisms that underlie the ability to understand language. The current volume examines the perception and processing of speech from the perspective of the hearing system. The chapters in this book describe a comprehensive set of approaches to the scientific study of speech and hearing, ranging from anatomy and physiology, to psychophysics and perception, and computational modeling. The auditory basis of speech is examined within a biological and an evolutionary context, and its relevance to applied domains such as communication disorders and speech technology discussed in detail. This volume will be of interest to scientists, engineers, and clinicians whose professional work pertains to any aspect of spoken language or hearing science.